DESENVOLVIMENTO DE UM EQUIPAMENTO DE SPIN COATING COM SISTEMA DE FIXAÇÃO DE SUBSTRATO A VÁCUO EMPREGANDO MATERIAIS REUTILIZADOS - Antonio A. A. Chepluki; Tiago E. A. Frizon; Igor E. de Carvalho (Química Nova, 2023)
This work presents the development of a low-cost spin coater for thin film deposition as an alternative to commercial equipment that have high acquisition cost. The proposed spin coater uses a brushless motor taken from an unused hard disk, which is activated through the association of an electronic speed controller (ESC) and an Arduino microcontroller. During deposition, the rotating substrate is attached with a vacuum clamping system. For the control, the system uses a Hall effect sensor to read the engine speed. The rotation readings performed by the equipment sensor were validated with a tachometer. Finally, TiO2 films were deposited on glass substrates with ITO (Indium Tin Oxide) and characterized by UV-Vis spectroscopy to obtain the transmittance of the films at different rotation speeds.